Engagement Perception of Young Lecturers Managerial Level at Business School PHU - Barry, Rinto Rain; Meilani, Cahya Palupi; Wuisan, Dewi S.; Meranga, Isana S.C; Bernarto, Innocentius (MEC-J (Management and Economics Journal), 2020)
The study aimed to determine the perception of engagement of young lecturers belongs to the millennial generation (born 1986-2000) at the managerial level in Business School PHU. They are based on the millennial lecturer's experience while being managerial and what is felt in employee engagement. Likewise, with Business School PHU, which is engaged to the institution, will help Business School PHU gained higher performance. The lecturer is an essential thing in the learning process. At the same time, Business School PHU has the majority of millennials lecturers. Business School PHU hopes that employees of the millennial generation can survive, have long-term commitments. Business School PHU should be able to make them feel at home and feel comfortable working. There is a fair adaptation process in terms of Human Resource Management across different generations.Data collection through triangulation and (literature study, in-depth interviews, observation). Informants consist of two categories: (1) three millennial managers who have worked more than two years at Business School PHU and has Academic Position, minimal Expert Assistant; (2) their direct supervisors of the first category.Â  Processing data by making interview summaries to formulate patterns, categories, and variables then formulated in propositions for the proposed model. Research contributions are expected to provide input to the management of human resources in the private University context to build young lecturer level managerial engagement at the millennial generation's age